Pengaruh Pemberian Larutan Jahe Zingiber Officianale Roscoe terhadap Ektoparasit Lintah Hirudinea pada Ikan Kerapu Cantang Epinephelus Fuscoguttatus x Epinephelus Lenceolatus - RAKA PERMANA RAKA; Rika Wulandari; Aminatul Zahra (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2021)
Ginger (Zingiber officinale Roscoe) is a type of herbal ingredient that contains sineol compounds and phenylpropane derivatives. Phenylpropane is an aromatic compound that is antifungal and toxic to ectoparasites. This study aims to test the concentration of ginger solution against Hirudinea leeches in grouper fish. This research was conducted in February 2021 in the village of Tanjung continued. The identification of ectoparasites was carried out at the Marine Biotechnologt Laboratory FIKP. The method used in this study was analyzed using a completely randomized design (CRD) with 4 treatments and 3 replications with a concentration of 0%, 0.4%, 0.5% and 0.6%. The results showed that the type of ectoparasites that infested grouper fish was the Zeylanicobdella sp. and the results obtained from observations of ectoparasite reduction at 30 minutes were the highest in treatment C, the concentration of ginger sea was 0.6% with a decrease intensity of 0.33% individuals / head which was categorized as low.